Pre-hospital analgesia in pediatric trauma and critically ill patients: an analysis of a German air rescue service - Eimer, Christine; Reifferscheid, Florian Sebastian; Jung, Philipp; Rudolph, Marcus; Terboven, Tom; Hoffmann, Florian; Lorenzen, Ulf; Köser, Andrea; Seewald, Stephan (Scandinavian journal of trauma, resuscitation and emergency medicine, 2023)
Pain management in the pre-hospital setting remains a particular challenge for paramedics and emergency physicians, especially in children. This study evaluates the pre-hospital use and effect of analgesics in children with trauma or pain due to other reasons.
Gesehen am 21.04.2023